Cultural Physiology: Effect of Plant Growth Hormones on the Growth and Sporulation of Aspergillus umbrosus - Sood*, Manjulata (Journal of Phytology, 2011)
On the growth and sporulation of Aspergillus umbrosus (Bainier and Sartory) the effect of different plant growth hormones taken for studies, those were; indole-3-acetic acid (IAA), indole-3-butyric acid (IBA), napthyl acetic acid (NAA), gibberllic acid (GA), 6-benzyl adenine (BA) and kinetin. In each case the hormones were sterilized and filtration and added in the medium in 10, 15, 20 and 25 ppm concentrations after autoclaving. Results after experiments indicated that the plant growth hormones were adverse for the growth and sporulation of the fungus.